2013
DOI: 10.9790/0837-1824147
|View full text |Cite
|
Sign up to set email alerts
|

Reward Systems as Determinant Of Talent Management in Public Universities in Kenya

Abstract: The aim of this study was to determine whether reward systems influence talent management in public universities in Kenya. Literature has revealed that on one hand talent management has taken a slow pace or has lacked in institutions of higher education compared to the private sector on the other hand studies have established that reward systems in public institutions do not match the private sector. The sample was n=249 from public universities in Kenya. Factor analysis revealed a determinant of 0.144; Bartle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…What is more, a qualitative study was done still in Kenya by Gakure et al (2013) with an aim of finding out whether reward management influences talent management in Kenyan universities. The finding revealed that universities had attracted committed staff and managed to retain them.…”
Section: Findings Of Studies Done In Higher Education Institutionsmentioning
confidence: 99%
“…What is more, a qualitative study was done still in Kenya by Gakure et al (2013) with an aim of finding out whether reward management influences talent management in Kenyan universities. The finding revealed that universities had attracted committed staff and managed to retain them.…”
Section: Findings Of Studies Done In Higher Education Institutionsmentioning
confidence: 99%
“…Moreover, such challenges do not only affect institutional stability but also influence workers' movements for better chances and job security. Yet, it is empirically clear that through trained human resources, organisations can thrive amid these challenges and improve performance to better their position in the world market stage (Mary et al, 2015;Mayer et al, 2014;Montanini, 2013;Gakure, 2013;Richards, 2012;Rudhumbu, 2014).…”
Section: The Nature Of Universities Practice Towards Talent Managementmentioning
confidence: 99%